(untitled) (Eurasian Research Bulletin, 2026)
This article discusses the improvement of administration based on bringing business entities to a new level, further increasing the population’s literacy in tax administration, supporting entrepreneurship, creating equal competition conditions and guaranteeing consumer rights, and encouraging the active participation of the general public in curbing the underground economy. In recent years, countries around the world have been paying special attention to the introduction of various mechanisms for preventing and reducing tax evasion by taxpayers when developing their short- and long-term budget and tax policy strategies. At the same time, reducing illegal financial flows, analyzing the factors that cause tax evasion by taxpayers, and conducting scientific research aimed at the scientific and theoretical aspects of tax evasion processes by reducing the underground economy remain one of the priority areas. At the same time, the areas were studied, foreign experience was used, scientific and practical conclusions and proposals were formulated on its application in our country